Extractive Spectrophotometric Determination of Cu(II) with 4-Chloron Isonitroso Acetophenone Thiosemicarbazone - Lokhande, R.S.; Poman, S.V.; Kapadi, U.R. (Asian Journal of Chemistry, 2010)
A method is proposed for the extraction and spectrophotometric determination of Cu(II) at microgram levels by using 4-chloro isonitroso acetophenone thiosemicarbazone (CINAPT) as an analytical reagent. Cu(ll) forms reddish complex with CINAPT which can be extracted in chloroform in the pH range 7.5 to 8.5 under optimum conditions. The chloroform extract shows maximum absorbance at 400 nm wavelength. Beer's law is obeyed over the range of 0.2 to 20 microgram per mL of Cu(II). The molar absorptivity is 2.518 x 103 L mol-1 cm-1. The composition of the species is found to have 1: 2 (metal : ligand) stoichiometry. Interference due to diverse cations and anions has been investigated. The method has been applied for the determination of copper in alloys and pharmaceutical samples.